PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN MOTIVASI BELAJAR IPA PESERTA DIDIK KELAS VI UPT SD INPRES PARANG - Alifah Dhiah Qanifah; Asmirah Khusnul khatimah; Nur Azmi; Wahyuni Antasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to determine the increase in science learning motivation of class VI.A UPT SD Inpres Parang students who are taught by applying the Project Based Learning model. The type of research used is Classroom Action Research (PTK) which consists of two cycles with stages including Planning, Implementation, Observation-Evaluation, and Reflection using a qualitative approach. The research subjects were students of class VI UPT SD Inpres Parang Makassar city district. The population in this study were all grade VI UPT SD Inpres Parang in the 2024/2025 school year. The research sample taken was one class VI.A with 15 students. The results showed that the use of the Project Based Learning learning model can increase the Science Learning Motivation of Class VI UPT SD Inpres Parang students, we can see that in cycle I learning shows that the success indicator reaches the sufficient category (C) in cycle II learning motivation has reached the good category (B).